The effect of Work Stress, Job Satisfaction, and Perceived Alternative Employment Opportunities on Turnover Intention - Ferdinandus Constantio S; Wilson Bangun (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of perceived alternative employment opportunities (PAEO), job stress, and job satisfaction on turnover intention among employees of Company X, one of the largest distribution companies in Indonesia. The issue of employee turnover in this company is quite significant, with data showing thousands of resignations between 2008 and 2024, primarily due to employees moving to other companies or starting their own businesses. This research employs a quantitative approach using a survey method involving 263 employees in the southern region of West Java, calculated by Issac and Michael formula and taken by statified random sampling technique. Data are collected using a seven-point Likert scale questionnaire and analyzed using a covariance-based structural equation modeling (CBSEM) approach. The results of this study are expected to test three main hypotheses: (1) PAEO has a positive effect on turnover intention, (2) job stress has a positive effect on turnover intention, and (3) job satisfaction can reduce turnover intention. These findings are expected to strengthen the literature on human resource management, particularly in efforts to reduce turnover rates through strategies to increase job satisfaction and manage stress, as well as to address employees’ perceptions of external employment opportunities. FMCG Company’s management can utilize the practical implications of this research to formulate more effective employee retention policies.